The role of scapholunate interosseous, dorsal intercarpal, and radiolunate ligaments in wrist biomechanics. (26th August 2021) - Badida, Rohit; Akhbari, Bardiya; Vutescu, Emil; Moore, Douglas C.; Wolfe, Scott W.; Crisco, Joseph J.
Abstract: Rupture to wrist ligaments predisposes the joint to degenerative changes. Scapholunate interosseous ligament (SLIL) rupture, especially when compounded by dorsal intercarpal ligament (DIC) and long radiolunate ligament (LRL) disruption, can cause carpal bone kinematic abnormalities. It is essential to delineate the role of these ligaments and their constraints on wrist range-of-motion (ROM) and center of rotation (COR). Wrist ROM and COR location were determined in 9 specimens using a six degree-of-freedom robotic musculoskeletal simulator in 24 directions of wrist motion for four experimental conditions: intact, and after sequential sectioning of the SLIL, DIC, and LRL. Sectioning the SLIL alone did not change wrist ROM in any direction (p > 0.10), while sectioning the SLIL and both the DIC and LRL caused significant increases in radial deviation, radial-extension, and ulnar-flexion ROM (p < 0.05). The COR of the intact wrist was located between the proximal third and middle third of the capitate, depending on the direction of wrist motion. While SLIL sectioning alone did not affect the COR, subsequent DIC sectioning led to a distal shift of COR in motions involving ulnar-extension relative to the intact condition. Additional sectioning of the LRL caused a proximal shift of COR in motions involving radial-flexion. A proximal shift implies a more dominant role of the radiocarpal joint, while a distal shift of the COR implies an increased role for the midcarpal joint. Understanding the role of ligaments on overall wrist mechanics is critical to devising new treatment strategies to restore wrist function.